2015
DOI: 10.1007/s12665-015-4577-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of submarine groundwater discharge on seawater properties in Rovanjska-Modrič karst region (Croatia)

Abstract: Coastal karst aquifers are dynamic hydrogeological systems with substantial hydrological, geomorphological and ecological impacts on the marine and coastal karst ecosystems, mostly induced by the submarine groundwater discharge (SGD). This paper presents complex hydrogeological settings of the Rovanjska-Modrič coastal karst region on the eastern Adriatic coast characterized by: (1) high temporal and spatial variations in seawater properties; (2) significantly reshaped coastal bottom morphology, and (3) plethor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Focused SGD with an expected circular to elliptical shape as observed by Mallast et al (2014) and Swarzenski et al (2001), are not unequivocally visible from the single frame (one thermal radiance image) only. At the upper and left ends of the single frame (first frame in Fig.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Focused SGD with an expected circular to elliptical shape as observed by Mallast et al (2014) and Swarzenski et al (2001), are not unequivocally visible from the single frame (one thermal radiance image) only. At the upper and left ends of the single frame (first frame in Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Once the ascending mixture reaches the lake's surface, it develops a radially orientated flow away from its jet centre, causing a circular-like pattern. These patterns are partially visually observable as shown in Mallast et al (2014) at the Dead Sea and in various other cases (Swarzenski et al, 2001).…”
Section: Submarine Groundwater Discharge and Onshore Spring Charactermentioning
confidence: 80%
See 1 more Smart Citation
“…Seawater properties in the shallow eastern coastal Adriatic are exposed to high temporal and 99 spatial variations mainly characterized by large temperature fluctuations and freshwater inputs 100 (e.g. Ogrinc et al, 2005;Surić et al, 2015). The intrusion of freshwater is more evident in river 101 mouth areas, where also the incorporation of nutrients and organic matter from terrestrial origin 102 stimulates biological productivity and creates a characteristic fluctuating environment.…”
Section: Introduction 30mentioning
confidence: 99%
“…Water in such caves is highly polluted and can cause serious health conditions in humans, either through consumption of such water or through contact of injured skin and water, which enables entrance of bacteria into blood. The study in Modrič Cave (30 km NE of the town of Zadar) showed that the guano deposits are responsible for significantly elevated values of heavy metals (Cu, Cd and Zn) in both cave sediments and percolating water (Miko et al, 2002), and probably in the adjoining sea water (Surić et al, 2015). Humans can also bring bacteria into caves.…”
Section: Introductionmentioning
confidence: 99%